Linking market orientation and service relatedness to new service development: The case of Italian small accounting firms - Maurizio Massaro; Gina Rossi; Carlo Bagnoli (The International Journal of Management Science and Information Technology (IJMSIT), 2015)
Small and Medium Accounting Practice Firms (SMPs) are crucial in helping SMEs to keep their businesses economically and financially sustainable. Although the importance of SMPs for fostering SMEs daily activities is growing, a general lack in terms of literature has been recognized. Innovation in the service sector is characterized by distinctive features, and literature on product innovation cannot be applied verbatim. Several studies have recognized the importance of Market Orientation to support product innovation while less attention has been paid by the service industry. In addition, previous studies seem to consider product innovation as a general construct without considering the impact of the relatedness. Applying the Person-Environment theory (PE), this study analyzes the impact of Market Orientation (MO) on New Service Development (NSD), distinguishing new services according to their relatedness to already provided ones. A logistic regression on a sample of 960 fully filled in questionnaires has been used. Results show that Market Orientation has a significantly different impact on related and unrelated diversification. The study aims to contribute to existing literature by helping to achieve a better understanding of diversification activities in SMPs. At the same time, the study wants to offer empirical evidence that could lead to recognizing best practices in NSD.
Keywords: 650; New Service Development; Market Orientation; Small Accounting Practices; Innovation; Relatedness